Frame-sliced voxel representation: An accurate and memory-efficient modeling method for workpiece geometry in machining simulation. (July 2017) - Joy, Jimin; Feng, Hsi-Yung
Abstract: This paper presents a new and enhanced voxel representation format for modeling the machined workpiece geometry in simulating machining operations involving repeated update of the workpiece model volume. The modeling format is named as the Frame-Sliced Voxel representation (FSV-rep) as it uses a novel concept of frame-sliced voxels to represent the boundary of the workpiece volume. The FSV-rep uses a multi-level surface voxel representation for sparse and memory-efficient implementations. The utilization of frame-sliced voxels enables approximation of the workpiece surface to only loosely depend on the grid resolution but achieve sub-voxel resolution updates for the model volume. It can, thus, provide a boundary representation of the workpiece model at an accuracy that is much higher than a basic voxel model of the same grid resolution and a similar model size. Quantitative comparisons of the FSV-rep with the traditional voxel representations at the same finest grid resolution show improvement up to two orders of magnitude in accuracy with only marginal increases in the model size. This confirms the effectiveness of the FSV-rep in simulating machined workpiece geometry in complex machining processes such as multi-axis milling. Highlights: A new method to model the machined workpiece geometry in milling simulation. Applicable to all milling processes including multi-axis free-form surface machining. Sparse multi-level surface voxel model size with triangle mesh model accuracy.